Trade uncertainty in US and China on trade openness in Sub-Saharan Africa. Issue 1 (2nd January 2022) - Bandura, Witness Nyasha
ABSTRACT: This study applies the system GMM technique to determine the impact of external trade uncertainty on trade openness for 35 countries in Sub-Saharan Africa, over the period 1985–2019 with 5-year non-overlapping data. Given the rapid globalisation and episodes of global economic uncertainty over the recent years, the research attempts to identify if trade uncertainty from outside of the region could affect trade openness in the region. There is strong evidence of a negative impact of trade uncertainty from both China, the US and the world on trade in Sub-Saharan Africa. The negative impact is, however, more severe from the world and followed by China. Comparatively, it can be concluded that China is more influential on Africa's trade as compared to the US. It is, therefore, recommended that African economies should be concerned with trade uncertainty from around the world and put in place some measures to safeguard their economies.